Economic growth, environmental sustainability, and human needs: A firm-level analysis - Alharithi, Mohammed (Ecological Questions, 2025)
We examine how renewable energy adoption (REA) and social welfare (SW) initiatives shape corporate profitability in Saudi Arabia, a critical test case for resource-dependent economies undergoing sustainability transitions under Vision 2030. Employing a dynamic panel Generalized Method of Moments model and quartile regression on 48 firms (2010–2024), the analysis dissects heterogeneous effects across low-, mid-, and high-profitability tiers. Results reveal that RE adoption drives profitability most for high-profit firms, leveraging scalable infrastructure and innovation, while SW initiatives like job creation and training disproportionately benefit low-profit firms by stabilizing operations. Mid-profit firms uniquely capitalize on RE-SW synergies, balancing green innovation with workforce development. These findings challenge narratives of sustainability as a profitability trade-off, aligning with the Porter Hypothesis and Stakeholder Theory. Policy implications advocate for tiered strategies: RE incentives for high-profit firms, training subsidies for low-profit firms, and synergy-focused industrial zones for mid-profit firms. By tailoring interventions to financial contexts, Saudi Arabia can harmonize Vision 2030’s sustainability goals with equitable growth, offering a model for resource-rich economies navigating green transitions.